Parents as Teachers Amid Christian Families - Simanjuntak, Joksan (International Journal Labs, 2025)
The Great Commission is the last command of Jesus Christ to His disciples before ascending to heaven. This Great Commission is stated in the Gospel of Matthew 28:19-20. This sacred mandate calls every believer to remain steadfast and actively participate in it (cf. 2 Timothy 4:2a). In this context, the mission extends beyond reaching those far from Christian circles or confined to those outside the home. It also applies to reaching those within families, particularly in how to reach children, who are a gift from God, and need to receive the touch of this Great Commission. Regarding this, the research is aimed at examining: What is the biblical theological concept of family for Christians? How is the biblical theological concept of parents' role as spiritual educators applied within the family? What is the essence of the biblical theological teaching role within the family? What are the challenges faced by parents as educators within the family? The study employs qualitative research with a literature review approach. This study reveals that parents, as primary educators within the Christian family, play an essential role in imparting spiritual education to their children. The research highlights that despite challenges such as cultural shifts and the pressure of modern life, the biblical mandate for parents to guide their children in faith remains critical for fostering a strong Christian identity within the family.